Editorial special issue RE 2017 - Hayes, Jane; Paech, Barbara (Requirements engineering, 2018)
This special issue of the Requirements Engineering Journal (REJ) spotlights top papers from the 25th IEEE Requirements Engineering Conference (RE 2017), extended to journal length. There is a long-standing tradition of the REJ to invite authors of the best papers from the RE conference to prepare journal length papers to reach a wide readership. It is our honor, as RE 2017 Program Co-Chairs, to introduce these papers.
Gesehen am 11.12.2019